To investigate thermal conductivity and viscosity of Al2O3/ R-11 nanorefrigerant - Dhindsa, Gurpinder Singh (My University, 2013)
Nanorefrigerant is one kind of nanofluids that seems to be possessing better heat transfer performance over traditional refrigerants. Thermal conductivity & viscosity are important thermophysical properties of the refrigeration which affects its performance. Experimental investigations are done on thermal conductivity and viscosity of Al2O3/R-11 nanorefrigerant at different weight concentrations and temperature with varying size and shape of nanoparticles. Al2O3 (20 nm-spherical, 40 nm-spherical and 40 nm-elongated)nanoparticles are mixed with the refrigerant R-11 at varying concentration (0.02-0.10 wt.%) using ultrasonic vibration. The objective of this study is to investigate the dependence of thermal conductivity and viscosity of Al2O3–R11 nanorefrigerant on temperature (4-16°C) at different weight concentrations, shape (spherical & elongated) and size (20 nm & 40 nm). As use of nanorefrigerant is in the initial stage, it has been observed in literature that there are significant discrepancies in the reported data about nanorefrigerant thermal conductivity and viscosity. A detailed literature review is coined about the unique features of nanofluids, such as their preparation, viscosity and thermal conductivity. Experimental studies are discussed in terms of the effects of various parameters such as particle volume fraction, particle size and temperature on the thermal conductivity and viscosity of nanofluids/nanorefrigerants. Based on the experimental analysis it is observed that thermal conductivity and viscosity augmented significantly with the increase of weight concentrations. Thermal conductivity increase around 42% at 0.10 wt. % (4°C) of 40 nm elongated Al2O3 nanoparticles and viscosity up to 31%. A nonlinear relationship is observed of thermal conductivity and viscosity with increment of particle weight concentrations for 40 nm (elongated) nanoparticles. The absolute thermal conductivity and viscosity of nanorefrigerant decrease with temperature (4-16°C) in both the base fluids (R-11) and the nanorefrigerant (Al2O3/R-11). But the relative viscosity remains almost invariant within variation of 1-2% with increase in temperature. Al2O3 nanoparticles of size 20 nm have more thermal conductivity & viscosity than 40 nm nanoparticles within measured temperature range (4-16°C). Also, the thermal conductivity & viscosity enhancement of nanorefrigerant with elongated shaped Al2O3 nanoparticles (40 nm) is more than spherical shaped (40 nm) Al2O3 nanoparticles within measured temperature range (4-6°C).Therefore, low weight concentration (up to 0.08 wt.%) of 20 nm (spherical) size nanoparticles is suggested to improve the performance of a refrigeration system in the temperature range from 4-16°C.
Master of Engineering-Thermal, Dissertation
Keywords: nanorefrigerant; nanoparticle; thermal conductivity; viscosity; R-11